Antioxidant activity and total phenolic content from liquid-liquid extraction of manuka, kelulut and pineapple honey / Muhammad Hanif Adli Mohd Asri - Mohd Asri, Muhammad Hanif Adli (2014)
Honey is known for various resources by numbers of societies in the world. The benefits and uses of honey have been studied for many centuries. For instance, ancient physicians of Greeks, Assyrians, Chinese, Roman and Egyptians have discovered combined honey with herbs are used to treat wounds and gut diseases (Peter C. Molan, 1999). Although there are arguments among medical professional toward the uses and effectiveness of honey, a number of studies reported honey are effective in reducing the risk of getting cancer, heart disease, declined of immune system and some inflammations (Alvarez-Suarez et al., 2010).